2010
DOI: 10.1016/j.vaccine.2010.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Antibody responses elicited through homologous or heterologous prime-boost DNA and protein vaccinations differ in functional activity and avidity

Abstract: Using a gp120 envelope glycoprotein from the JR-FL strain of human immunodeficiency virus-1 (HIV-1) as a model antigen, the goal of the current study was to evaluate the level and quality of antibody responses elicited by different prime-boost vaccination regimens (protein only, DNA only, DNA plus protein) in rabbits. Our data demonstrated that incorporating DNA immunization as a prime in a heterologous prime boost regimen was able to elicit a more diverse and conformational epitope profile, higher antibody av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
77
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 30 publications
9
77
0
Order By: Relevance
“…Previously, we reported that DNA prime-protein boost could induce improved antibody responses targeting the CD4bs, as such sera could compete well against the broad neutralizing mAb, b12 (Vaine, Wang et al, 2008;Vaine, Wang et al, 2010). In the current study, the presence of CD4bs-specific antibodies in rabbit immune sera was also evaluated against the broadly neutralizing antibodies b12, VRC01 and VRC03.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we reported that DNA prime-protein boost could induce improved antibody responses targeting the CD4bs, as such sera could compete well against the broad neutralizing mAb, b12 (Vaine, Wang et al, 2008;Vaine, Wang et al, 2010). In the current study, the presence of CD4bs-specific antibodies in rabbit immune sera was also evaluated against the broadly neutralizing antibodies b12, VRC01 and VRC03.…”
Section: Resultsmentioning
confidence: 99%
“…This result confirmed our previous data that a CD4 binding site antibody, similar to b12, was elicited in rabbit studies using gp120 immunogens from subtypes other than subtype BC. 9,11 At the same time, rabbit sera elicited by subtype BC gp120 were unable to compete against VRC01 or VRC03. This finding is not completely unexpected as VRC01 or VRC03 has much broader neutralizing activities than b12 and b12 can only neutralizing viruses from certain subtypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, vaccinations in which DNA priming is followed by a recombinant viral vaccine boost can elicit greater immunity when compared to the use of single immunogens (Lu, 2009;Radaelli et al, 2003;Radaelli et al, 2007;Wang et al, 2008). Combined vaccines can also elicit improved antigen-specific antibody responses (Vaine et al, 2010).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…A DNA prime, adenoviral serotype 5 (Ad5) vector boost vaccine expressing multiclade Env inserts elicited a greater breadth of NAbs than that of a comparator single Env immunogen (30,31). Similarly, a multiclade DNA prime, gp120 protein boost vaccine elicited a greater breadth of NAbs than that of the comparator single gp120 immunogen in rabbits (32,33). However, these previous studies did not directly compare the cocktail with each individual component of the vaccine; thus, the potential advantage of an Env immunogen cocktail remains unclear.…”
mentioning
confidence: 99%